A Therapeutic Strategy to Combat HIV-1 Latently Infected Cells With a Combination of Latency-Reversing Agents Containing DAG-Lactone PKC Activators - Matsuda, Kouki; Kobayakawa, Takuya; Kariya, Ryusho; Tsuchiya, Kiyoto; Ryu, Shoraku; Tsuji, Kohei; Ishii, Takahiro; Gatanaga, Hiroyuki; Yoshimura, Kazuhisa; Okada, Seiji; Hamada, Akinobu; Mitsuya, Hiroaki; et al. (Frontiers in Microbiology, 2021)
Advances in antiviral therapy have dramatically improved the therapeutic effects on human immunodeficiency virus type 1 (HIV-1) infection. However, even with potent combined antiretroviral therapy, HIV-1 latently infected cells cannot be fully eradicated. Latency-reversing agents (LRAs) are considered a potential tool for eliminating such cells; however, recent in vitro and in vivo studies have raised serious concerns regarding the efficacy and safety of the “shock and kill” strategy using LRAs. In the present study, we examined the activity and safety of a panel of protein kinase C (PKC) activators with a diacylglycerol (DAG)-lactone structure that mimics DAG, an endogenous ligand for PKC isozymes. YSE028, a DAG-lactone derivative, reversed HIV-1 latency in vitro when tested using HIV-1 latently infected cells (e.g., ACH2 and J-Lat cells) and primary cells from HIV-1-infected individuals. The activity of YSE028 in reversing HIV-1 latency was synergistically enhanced when combined with JQ1, a bromodomain and extra-terminal inhibitor LRA. DAG-lactone PKC activators also induced caspase-mediated apoptosis, specifically in HIV-1 latently infected cells. In addition, these DAG-lactone PKC activators showed minimal toxicity in vitro and in vivo. These data suggest that DAG-lactone PKC activators may serve as potential candidates for combination therapy against HIV-1 latently infected cells, especially when combined with other LRAs with a different mechanism, to minimize side effects and achieve maximum efficacy in various reservoir cells of the whole body.